Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41388-020-1318-0
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of WBP2 oncogene in human cancers

Abstract: WW domain-binding protein 2 (WBP2) is an emerging oncoprotein. Over the past decade, WBP2 surfaced as a key node connecting key signaling pathways associated with ER/PR, EGFR, PI 3 K, Hippo, and Wnt in cancer. In addition to the oncogenic functions of WBP2, this review discusses the latest research regarding the multilevel regulation and modes of action of WBP2 and how they can be exploited for molecular medicine. In translational research, evidence supports the role of WBP2 as a biomarker for early detection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 98 publications
2
36
0
Order By: Relevance
“…Patients with higher WBP2 expression had poorer overall and disease-free survival 15 . WBP2 is increasingly implicated in other cancers, such as skin, brain, and liver 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with higher WBP2 expression had poorer overall and disease-free survival 15 . WBP2 is increasingly implicated in other cancers, such as skin, brain, and liver 10 .…”
Section: Introductionmentioning
confidence: 99%
“…W W domain- B inding P rotein 2 (WBP2) was first identified as a cognate ligand of the WW domain of YAP 8 , 9 . WBP2’s transcription co-activator function is important to cancer 10 . Binding of WBP2 to E6AP potentiated Estrogen and Progesterone Receptor co-activation 11 by binding to the phosphorylated form of RNA polymerase II and histone acetyltransferase p300 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The upstream protein WWC3 of the Hippo pathway was identi ed as WBP2 binding protein Previous studies suggested that WBP2 localizes within the nucleus of breast cancer cells and acts as a co-activator of YAP to promote the transcription of downstream genes [17]. Interestingly, we found that WBP2 was localized within the cytoplasm of lung cancer cells, and based on this, we speculated that WBP2 may modulate the Hippo pathway in a YAP-indirect-dependent manner.…”
Section: Cascade Phosphorylation Of the Mst-lats Complex In The Hippomentioning
confidence: 67%
“…WBP2 can bind to estrogen and progesterone receptors and can act as a co-activator of estrogen receptor (ER) and progesterone receptor (PR) hormone signaling transduction [12][13][14][15]. Additionally, the synergetic effect of WBP2 and YAP/TAZ in the nucleus plays an important role in promoting the proliferation and invasion of breast cancer cells by regulating the activities of classical signal pathways in both tumor tissues and normal tissues [16][17][18][19][20]. However, the expression pattern of WBP2 in lung cancer and the ability of this protein to regulate the activity of the Hippo pathway in an indirect manner that is dependent upon YAP both remain unreported.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several wellknown cancer migration and progression drivers were downregulated (Fig. 4B), including TRIM47 which mediates cancer migration 29 , the bona fide oncoprotein and potential biomarker WBP2 30 , and frequently highly amplified oncogene FNDC3B 31 . None of these proteins have previously been functionally linked to BRAT1.…”
mentioning
confidence: 99%